Propuesta para un método de reducción de carbono orgánico total para el sistema de distribución de agua potable (2020)
The interest generated in recent years to optimize the quality of drinking water has encouraged the search for improvements in the processes conventionally implemented to treat water, which leads studies to investigate the main sources of contamination and the variables that affect the process preventing the expectation of the quality that should be met from being met; therefore one of the main causes is found through the distribution networks, where there is a high probability of containing organic matter introduced for reasons exogenous to the treatment process such as permanent or transient pressure changes, even through the operation of valves and pumps in the network. This implies a risk and exposes the quality of drinking water to the multiple reactions that can occur, forming disinfection by-products due to the oxidation of organic matter by the disinfectants used. Through epidemiological and toxicity analyzes, SPD has been found in drinking water sources, which causes a high concern for human health, since it has been shown that these compounds can affect cell viability, as well as influence the formation of different types of tumors in the body and chronic diseases.